Twig biomass allocation of Betula platyphylla in different habitats in Wudalianchi Volcano, northeast China - Yang Fan (De Gruyter, 2021)
Understanding the response of biomass allocation in current-year twigs is crucial for elucidating the plant life-history strategies under heterogeneous volcanic habitats. We aimed to test whether twig biomass allocation, within-leaf biomass allocation, and the size-number trade-off of Betula platyphylla would be influenced. We measured twig traits of B. platyphylla in Wudalianchi volcanic kipuka, the lava platform, and Shankou lake in northeastern China using standardized major axis analyses. The results showed that the leaf number, total lamina mass (TLAM), stem mass (SM), and twig mass (TM) were significantly different between the three habitats and were greatest in kipuka with abundant soil nutrients. TLAM and SM scaled allometrically with respect to TM, while the normalization constants of the lava platform differ significantly between kipuka and Shankou lake, which showed that under certain TM, leaves gain more biomass in the lava platform. However, within the leaf, individual lamina mass (ILM) scaled isometrically with respect to individual petiole mass (IPM) in kipuka and the lava platform, but ILM scaled allometrically to IPM in Shankou lake. Our results indicated that inhabitats influenced the twig traits and biomass allocation and within-leaf biomass allocation are strategies for plants to adapt to volcanic heterogeneous habitats.